Consumption of alcoholic beverages, driving vehicles, a balance of dry law, Brazil 2007-2013 - Malta, Deborah Carvalho; Berna, Regina Tomie Ivata; Silva, Marta Maria Alves da; Claro, Rafael Moreira; Silva Júnior, Jarbas Barbosa da; Reis, Ademar Arthur Chioro dos (Revista de Saúde Pública, 2014)
The study analyzes the trend in frequency of adults who drive under the influence of alcohol in major Brazilian cities after the passing of laws, which prohibit drunk driving. Data from the Surveillance System for Risk and Protective Factors for Chronic Diseases by Telephone Survey (VIGITEL) between 2007 and 2013 were analyzed. The frequency of adults who drove after abusive alcohol consumption was reduced by 45.0% during this period (2.0% in 2007 to 1.1% in 2013). Between 2007 and 2008 (-0.5%) and between 2012 and 2013 (-0.5%), significant reductions were observed in the years immediately after the publication of these laws that prohibit drunk driving. These improvements towards the control of drunk driving show a change in the Brazilian population’s lifestyle.